2021
DOI: 10.1155/2021/9141695
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sweet Almond Oil Content of Four European Cultivars (Ferragnes, Ferraduel, Fournat, and Marcona) Recently Introduced in Morocco

Abstract: This study concerns the characterization of oil content and quality indices for almond cultivars (Marcona (Mr), Fournat (Fn), Ferragnes (Fg), and Ferraduel (Fd)) recently introduced into marginal agricultural areas in eastern Morocco. These verities are known for their rusticity and late flowering stage. The analyzed almond oils showed low acidity and peroxide values ranging, respectively, from 0.32 to 0.36% and 1.88 to 3.18 meq O2/kg. Fatty acid (FA) profile revealed a predominance of the unsaturated FA repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 63 publications
2
8
0
1
Order By: Relevance
“…According to Codex Alimentarius (2017), the parameters of quality of vegetable oils recommend that the peroxide index is the maximum 15 mEq of active oxygen/kg of virgin oil and the acidity index is the maximum of 2% AGL of oleic acid for oils unrefined. The peroxide index indicates the beginning of the oxidation of oils and fats, which are the primary lipid oxidation products (Melhaoui et al, 2021;Shahidi & Zhong, 2010;Zhang et al, 2023). The araticum seed oils, extracted by different methods, are below the limit established by Codex (2.67 ± 0.38 to 12 ± 0.15 mEq/kg), indicating efficient extraction quality in both methods used.…”
Section: Resultsmentioning
confidence: 99%
“…According to Codex Alimentarius (2017), the parameters of quality of vegetable oils recommend that the peroxide index is the maximum 15 mEq of active oxygen/kg of virgin oil and the acidity index is the maximum of 2% AGL of oleic acid for oils unrefined. The peroxide index indicates the beginning of the oxidation of oils and fats, which are the primary lipid oxidation products (Melhaoui et al, 2021;Shahidi & Zhong, 2010;Zhang et al, 2023). The araticum seed oils, extracted by different methods, are below the limit established by Codex (2.67 ± 0.38 to 12 ± 0.15 mEq/kg), indicating efficient extraction quality in both methods used.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding tocopherol contents, we have found 28.9 mg/kg of tocopherols in Baru oil, In fact, the tocopherol content is low when compared to other almond oils, such as Fournat, Ferraduel, and Ferragnes [ 25 ]. Although it is not possible to state the reason for this difference, a recent study demonstrated that the conditions of Baru oil extraction could interfere with tocopherol contents [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the results, it was found that PDBO contains 51.86 ± 3.97 mg GAE/kg TPC. The oil extracted from the almond nut of Prunus dulcis contains 85.33-141.66 mg/kg TPC [58], while almond as a nut contains 392.00-11,030.50 mg/kg TPC [59]. Noteworthy is that almond polyphenols are mostly found in the skin, with values ranging from 9100.00 to 32,100.00 mg/kg TPC [60].…”
Section: Total Polyphenol Content (Tpc) and Total Carotenoid Content ...mentioning
confidence: 99%